Segmental foot and ankle kinematic differences between rectus, planus, and cavus foot types. (20th September 2019) - Kruger, Karen M.; Graf, Adam; Flanagan, Ann; McHenry, Benjamin D.; Altiok, Haluk; Smith, Peter A.; Harris, Gerald F.; Krzak, Joseph J.
Abstract: The presence of multiple foot types has been used to explain the variability of foot structure observed among healthy adults. These foot types were determined by specific static morphologic features and included rectus (well aligned hindfoot/forefoot), planus (low arched), and cavus (high arched) foot types. Unique biomechanical characteristics of these foot types have been identified but reported differences in segmental foot kinematics among them has been inconsistent due to differences in neutral referencing and evaluation of only select discrete variables. This study used the radiographically-indexed Milwaukee Foot Model to evaluate differences in segmental foot kinematics among healthy adults with rectus, planus, and cavus feet based on the true bony alignment between segments. Based on the definitions of the individual foot types and due to conflicting results in previous literature, the primary study outcome was peak coronal hindfoot position during stance phase. Additionally, locally weighted regression smoothing with alpha-adjusted serial t -test analysis (LAAST) was used to compare these foot types across the entire gait cycle. Average peak hindfoot inversion was −1.6° ± 5.1°, 6.7° ± 3.5°, and 13.6° ± 4.6°, for the Planus, Rectus, and Cavus Groups, respectively. There were significant differences among all comparisons. Differences were observed between the Rectus and Planus Groups and Cavus and Planus Groups throughout the gait cycle. Additionally, the Planus Group had a premature peak velocity toward coronal varus and early transition toward valgus, likely due to a deficient windlass mechanism. This assessment of kinematic data across the gait cycle can help understand differences in dynamic foot function among foot types.